Neighbourhood socioeconomic circumstances, adiposity and cardiometabolic risk measures in children with severe obesity. Issue 4 (July 2019) - Juonala, Markus; Harcourt, Brooke E.; Saner, Christoph; Sethi, Manpreet; Saffery, Richard; Magnussen, Costan G.; Burgner, David P.; Sabin, Matthew A.
Abstract: Background: It has recently been shown that neighbourhood socioeconomic disadvantage in childhood is associated with obesity, hypertension, fatty liver, and type 2 diabetes in adulthood. However, it is largely unknown whether neighbourhood socioeconomic circumstances are important predictors of adiposity and associated measures in children, especially in those with severe obesity. Therefore, we evaluated the associations between neighbourhood socioeconomic factors with the severity of obesity, and related cardiometabolic risk factors in a cohort of obese children. Methods: The Childhood Overweight BioRepository of Australia (COBRA) cohort study comprises 444 children (mean age 11.1 years, mean BMI z-score 2.5). Neighbourhood socioeconomic advantage/disadvantage was evaluated based on postcode information by the national Australian Socio-Economic Indexes for Areas (SEIFA) scores. Participants/parents also completed self-administered questionnaires on neighbourhood related facilities, family education and family income. Results: In analyses adjusted for age, sex and pubertal status, SEIFA indicating neighbourhood education/occupation was negatively associated with BMI, waist circumference and body fat%. Higher family education was associated with lower BMI. Neighbourhood walkability was related to lower waist circumference. Good shopping facilities in the neighbourhood were associated with increased risk of dyslipidemia and fatty liver, and the existence of parks and playgrounds nearby was related to dyslipidemia. Conclusions: The present data suggest that neighbourhood-related issues are associated with less severe adiposity among children with established obesity. Concerning cardiometabolic risk factors, shopping facilities were related to dyslipidemia and fatty liver. These findings suggest that increased awareness and efforts are needed to diminish socioeconomic inequalities between neighbourhoods.